Food choices and practices during pregnancy of immigrant and Aboriginal women in Canada: a study protocol - Higginbottom Gina MA; Vallianatos Helen; Forgeron Joan; Gibbons Donna; Malhi Rebecca; Mamede Fabiana (BMC, 2011)
Abstract Background Facilitating the provision of appropriate health care for immigrant and Aboriginal populations in Canada is critical for maximizing health potential and well-being. Numerous reports describe heightened risks of poor maternal and birth outcomes for immigrant and Aboriginal women. Many of these outcomes may relate to food consumption/practices and thus may be obviated through provision of resources which suit the women's ethnocultural preferences. This project aims to understand ethnocultural food and health practices of Aboriginal and immigrant women, and how these intersect with respect to the legacy of Aboriginal colonialism and to the social contexts of cultural adaptation and adjustment of immigrants. The findings will inform the development of visual tools for health promotion by practitioners. Methods/Design This four-phase study employs a case study design allowing for multiple means of data collection and different units of analysis. Phase 1 consists of a scoping review of the literature. Phases 2 and 3 incorporate pictorial representations of food choices (photovoice in Phase 2) with semi-structured photo-elicited interviews (in Phase 3). The findings from Phases 1-3 and consultations with key stakeholders will generate key understandings for Phase 4, the production of culturally appropriate visual tools. For the scoping review, an emerging methodological framework will be utilized in addition to systematic review guidelines. A research librarian will assist with the search strategy and retrieval of literature. For Phases 2 and 3, recruitment of 20-24 women will be facilitated by team member affiliations at perinatal clinics in one of the city's most diverse neighbourhoods. The interviews will reveal culturally normative practices surrounding maternal food choices and consumption, including how women negotiate these practices within their own worldview and experiences. A structured and comprehensive integrated knowledge translation plan has been formulated. Discussion The findings of this study will provide practitioners with an understanding of the cultural differences that affect women's dietary choices during maternity. We expect that the developed resources will be of immediate use within the women's units and will enhance counseling efforts. Wide dissemination of outputs may have a greater long term impact in the primary and secondary prevention of these high risk conditions.